An annotated checklist of the genus Tristagma (Amaryllidaceae, Allioideae) - Arroyo-Leuenberger, Silvia C.; Sassone, Agostina B. (Phytotaxa, 2016)
Tristagma is a South American genus distributed in Argentina and Chile. Species circumscription in Tristagma has been a source of confusion for various reasons; e.g., generic concepts, nomenclatural inconsistencies, and doubtful species. As a first step towards a revision of Tristagma, the nomenclatural history is reviewed. Following an extensive review of specimens in various American and European herbaria, a generic description and a list of names and their types are here provided. Thirteen names are lectotypified, seven are synonymized, three holotypes are identified for the first time, one neotype is designated, a new combination is made, and 12 species are recognized: T. ameghinoi, T. anemophilum, T. berteroi, T. bivalve, T. circinatum, T. gracile, T. graminifolium, T. nivale, T. patagonicum, T. poeppigianum, T. porrifolium, and T. violaceum. A new record of the flora of Chile: T. circinatum is also reported. Additionally, five doubtful species are mentioned and three are excluded from Tristagma. Another five species names referred in the literature to Tristagma have already been transferred to other genera. We also provide conservation assessments, distribution maps and an identification key to species.